Lapatinib and Platinum-based Chemotherapy Ameliorate Breast Cancer with Choroidal Metastasis and Restore Visual Acuity. Issue 3 (May 2014) - Ju, Uei-Han; Tsai, Ming-Ling; Lin, Chun-Shu; Chao, Tsu-Yi; Dai, Ming-Shen
Involvement of the central nervous system in metastatic breast cancer is a particularly dismal occurrence because of its effects on mortality and quality of life. Development of choroidal metastasis in a breast cancer patient indicates poor prognosis and has become the major life-limiting problem. Various treatment modalities for choroidal metastasis have been applied with different efficacy. Here we describe a patient with HER2-overexpressing breast cancer and limited choroidal metastasis who responded to an HER2 tyrosine kinase inhibitor after failure of radiotherapy and chemotherapy. Her visual acuity was completely and durably restored after the targeted therapy. This case provides a unique treatment experience of breast cancer with choroidal metastasis.